Volatility, Global Proxy Index, V-A-R: Empirical Study on Pakistan And China Stock Exchanges - Muhammad Arslan; Wajid Shakeel Ahmed; Mansoor Akhter (International Journal of Advances in Data and Information Systems, 2020)
This study postulates that propose global proxy index is a significant conduit to evaluate the shocks in volatile stock markets i.e. PSX and SSE, alike. The two separate models i.e. Log-GARCH (1, 1) and ARMA-GARCH (1, 1) have been used along with the value at risk (V-a-R) @ 5% criteria for choosing best-fitted model. The study results showed Log-GARCH (1, 1) model proves to the best. This study results are not driven by political-level risks and thus independent study can be conducted to evaluate the detrimental consequences on investment opportunities under volatile environments.